Sustainable use of laterite replaced with bottom ash as road construction materials - Uthairith Rochanavibhata; Sakda Lhajai; Pornkasem Jongpradist; Nattapong Makaratat; Guoqing Jing; Pitthaya Jamsawang (International Journal of Sustainable Engineering)
Bottom ash (BTA), a byproduct of burning coal in electric power plants, is often considered waste. Managing significant quantities of bottom ash remains a challenge. Laterite, commonly used in road construction, may not meet the required standards in some regions, necessitating the transport of higher-quality laterite from distant locations. This practice increases construction costs. This research explores the use of bottom ash and cement as replacements for laterite in pavement materials. The proportion of bottom ash used varied from 10 to 50% by dry weight of the laterite, while the cement contents were 1, 3, 5, and 7% by dry weight of the laterite-bottom ash mixture. The experiments included unconfined compressive strength, splitting tensile strength, California bearing ratio, and durability against wetting-drying cycles. The results indicate that the stabilised laterite significantly increases strength values—2 to 14 times greater than those of unstabilised laterite, with 20% bottom ash replacement yielding the best results. Microstructural analyses confirmed the strength test outcomes. Replacing laterite with bottom ash and cement proves to be a sustainable method for road construction, offering cost-effectiveness, conservation of natural resources, pollution reduction, and enhanced energy efficiency in accordance with the standards of the Department of Highways of Thailand.